A DESCRIPTIVE STUDY: PARENTING OF CHILDREN WITH SPECIAL NEEDS - Ersa Lanang Sanjaya; Dewi Retno Suminar; Nur Ainy Fardana (International Journal Labs, 2022)
The parenting of children with special needs is important in order that children can develop optimally within the parameters of their particular needs. However, parenting children with special needs can be challenging for parents as it is high-demand over a long period of time. The current study aims to provide an overview of the parenting of children with special needs and of factors that can assist parents in caring for their children with special needs. The research adopts quantitative descriptive methods using a questionnaire as the tool for data collection. Research respondents included 89 parents of children with special needs. The results of the study indicate that mothers are more involved in parenting. In addition, parents experience relatively high levels of stress, with the main sources of stress being the day-to-day demands of parenting and worrying about their children’s futures. Spousal support and religion can act as consolidating factors for parents in facing the challenges of parenting